Oxygen vacancies assisted LaFeO3 derived from metal organic frameworks endows a practical HCHO sensor with excellent sensing characteristics - Guo, Lulu; Zhao, Shushu; Yang, Guimao; Gao, Lifeng; Wu, Yanhong; Zhang, Xuguang (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
[Display omitted] •MOFs-derived oxygen vacancies-enriched LaFeO3 was designed via a fast and scalable fabrication approach.•The resultant M−LaFeO3 gas sensor exhibit excellent HCHO sensing performance at a low operating temperature of 160°C.•The increased oxygen vacancies play a vital role in promoting the adsorption and activation of O2 and HCHO molecules.•M−LaFeO3 sensor shows excellent application prospect in food safety assessment. Perovskite oxide semiconductors have attracted tremendous interest in gas sensing due to their promising properties of tunable active sites, excellent catalytic ability and good structural stability. Nevertheless, the rapid synthesis of perovskite oxides and controlled regulation of their surface oxygen vacancies remains a great challenge. Herein, we report a novel metal–organic frameworks (MOFs) self-template strategy for the rapid and large-scale preparation of LaFeO3 nanoparticles (M−LaFeO3) with abundant oxygen vacancies. Benefit from the introduction of oxygen vacancies, the resultant M−LaFeO3 gas sensor exhibit excellent formaldehyde (HCHO) sensing performance at a low operating temperature of 160 °C, including high sensitivity (Rg/Ra = 8.9 @ 100 ppm), fast response/recovery rate (53 s/32 s), low detection limit (1 ppm) and excellent selectivity. Comprehensive density functional theory (DFT) calculation and spectral characterizations reveal that oxygen vacancies play a vital role in promoting the adsorption and activation of O2 and HCHO molecules, and accelerate the chemical reaction on the sensing materials surface. Most importantly, it proves the promising application of M−LaFeO3 sensor in food safety assessment. This work not only provides a simple strategy for constructing oxygen vacancies enriched LaFeO3, but also demonstrates the application potential of LaFeO3-based gas sensors in the field of formaldehyde detection.